PENGARUH PENERAPAN ACCRUAL BASIS, KOMPETENSI SUMBER DAYA MANUSIA DAN PENGENDALIAN INTERNAL PEMERINTAH TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH KOTA LANGSA (Studi Pada Organisasi Perangkat Daerah Pemerintah Kota Langsa) - imelda imelda; hilmi hilmi; mursidah mursidah; rayyan firdaus (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Malikussaleh, 2024)
This research aims to determine the influence of the implementation of the Accrual Basis, human resource competency and the government's internal control system on the quality of Langsa City government financial reports. This research was conducted at the Regional Apparatus Organization (OPD) in Langsa City. The data used in this research is primary data obtained by distributing questionnaires to 78 respondents consisting of the Head of the Finance Sub-Division, Treasurer and Financial Staff at the Langsa City OPD. The data analysis method used is multiple linear regression analysis. The research results show that (1) the implementation of the Accrual Basis has a positive and significant effect on the quality of the Langsa City government's financial reports, (2) Human Resource Competency has a positive and significant effect on the quality of the Langsa City government's financial reports. (3) the government's internal control system has a positive and significant effect on the quality of Langsa city government's financial reports.